Surge Characteristics of Reservoir Bank Granular Landslide Based on Physical Model Experiments - Shanshan WANG; Jianzhao ZHANG; Dongpo WANG; Dongxu YANG; Weilin YUAN; Chaojun OUYANG (工程科学与技术)
Objective Landslide surge disasters have consistently been one of the significant geological and engineering challenges studied both domestically and internationally. Accurately evaluating the process of water surges caused by scattered particle landslides on mountainous reservoir banks and understanding the propagation law of surges in rivers is crucial. This study analyzes the characteristics of surge propagation laws, establishes a formula for calculating the maximum height of surges, and verifies it through typical cases of water surges caused by scattered particle landslides, providing a scientific basis for disaster prevention and reduction.Methods This study focuses on the instability of reservoir bank landslides and the process of water surges, considering two scenarios: water landslides and submerged landslides. Three-dimensional physical model experiments of granular landslide surges are designed and conducted. The landslide surge simulation system, combined with the geometric shapes of river channels in the Three Gorges, Jinsha River Xiluodu, Yalong River Lianghekou Hydropower Station, and other reservoir areas, established a generalized river channel model of typical wide and straight reservoir sections in the reservoir area based on a geometric similarity ratio of 1:500. The model primarily comprises a source release device, a bank slope, and a closed glass water tank, which can simulate the entire process of landslide initiation, water inflow, accumulation, wave generation, propagation, and climb. Through physical model experiments, the process of landslide inflow and accumulation, as well as the characteristics of wave generation and propagation, are measured. Additionally, the amplitude and propagation characteristics of offshore waves propagating along the direction of landslide movement and lateral waves propagating upstream and downstream along the river channel are analyzed.Results and Discussions This study designed and conducted 96 sets of working conditions and 192 experiments to measure and analyze the process of landslide inflow movement and accumulation, as well as the characteristics of wave generation and propagation. The following conclusions are drawn: the entire process of granular sliding into water and wave propagation can be divided into three stages: the granular sliding into water stage, the wave generation stage, and the wave propagation and climbing stage. By analyzing the amplitude data of the surging waves, it was observed that the maximum peak and trough of the offshore surging waves were generated by the first wave. During the propagation of lateral waves, due to the collision and superposition of reflections on both sides of the river and solid waves, the maximum peak and trough of the surging waves appeared in subsequent wave trains. When a landslide transitions from a submerged condition to a waterborne condition, the maximum amplitude characteristic of the surge wave changes from a peak smaller than the valley to a peak larger than the valley. The wave amplitude generated along the direction of landslide movement is greater than that propagated along the reservoir bank, and the attenuation degree of wave amplitude height during lateral wave propagation is smaller than that of offshore waves. At the same time, this study compared and analyzed the inflow waveforms of two types of landslides: granular and block landslides. From the perspective of inflow forms, block landslides, and granular landslides exhibit significant differences, mainly reflected in aspects such as water tongue formation, impact pits, and wave amplitude. Compared to granular landslides, block landslides form more pronounced impact craters when entering the water. The upper water body projects toward the opposite bank in a tongue-like shape and splashes onto the water surface or bank slope, while the lower water body begins to move from rest. Block landslides, due to their interaction with water bodies, instantly enter the water with a larger volume, transferring more energy to the water body and generating larger wave amplitudes, which result in greater harm. A granular landslide forms a slender motion pattern on a slope, with a relatively small volume entering the water instantly, making it difficult to generate jet flow. Under block landslide conditions, the amplitude of the surge wave exhibits a characteristic where the peak value is significantly larger than the valley value. In contrast, under granular landslide conditions, the peak and valley amplitudes are approximately equal. This study analyzed the characteristics of the first wave and its maximum height during lateral surges. Under normal circumstances, when the surge propagates along the upstream and downstream of the river channel, the maximum height of the lateral wave is 2.5 times the height of its first wave. Based on the measurement system used in this experiment, 192 sets of data on the maximum height of swells generated by the inflow of test particles were obtained. The dimensional analysis method was employed to select three factors: the relative mass of the landslide body, the relative inflow height difference, and the relative submergence depth. The relationship between these parameters and the maximum height of swells was examined. The experimental results indicated that the maximum height of the surge is positively correlated with the mass of the granular landslide and negatively correlated with the initial submergence rate of the granular landslide. Within the dimensional range set in the experiment, it was found that the maximum height of the surge was negatively correlated with the height difference of the dispersed particles entering the water. The analysis revealed that compared to block landslides entering water as a whole, granular landslides exhibit a greater degree of discretization when entering water. During the unstable movement of landslides, strong collision and friction between granular particles result in partial energy loss. During the overall movement of the granular landslide, it continuously spreads to both sides. As the relative height difference of the inflow increases, the cross-sectional area of the landslide body impacting the water body gradually decreases under a single width. The reduction in kinetic energy transmitted by the single-width landslide body entering the water is more significant than the change in potential energy. Therefore, under indoor test conditions, the impact energy obtained by the unit water body is lower. For granular landslides without lateral constraints in the motion path, the maximum height of the surge is negatively correlated with the inflow height. The relationship between the maximum height of the surge and various influencing factors was obtained using dimensionless methods and multiple linear regression analysis. The empirical formula results showed good consistency with the physical experimental results. The empirical formula derived in this study was applied to the actual cases of the Hongyanzi landslide and the Chehalis Lake landslide surge disaster in Canada. The empirical formulas proposed by domestic and foreign scholars were compared and discussed. The results indicate that the empirical formula proposed in this study aligns well with other empirical formulas when compared to actual observation results, demonstrating a certain degree of reliability and applicability.Conclusions The experiment designed in this study primarily focuses on landslide surges in typical wide and straight sections of the reservoir area. The empirical formula proposed is applicable to granular landslides or loose accumulations and serves as a theoretical reference for landslide surge disaster warnings in reservoir areas.